Successful Endoscopic Management of Complete Tracheal Occlusion in a Child - Bhavya Balaji; Aureen Ruby Dcunha; B. Sandeep Rai; B. H. Giridhar; Swathi Sunil Rao (Journal of Indian Association of Pediatric Surgeons)
Prolonged mechanical ventilation following cardiopulmonary and neurological events oftentimes necessitates a tracheostomy and tracheal granulation is one of its most common late complications. The literature recommends that large granulation be managed through surgical excision or endoluminal techniques. A 6-year-old boy presented with high-grade tracheal stenosis secondary to endotracheal cuff-related injury and prolonged tracheostomy. We present an unconventional yet successful method of management that included multiple sittings of endoscopic rigid bronchoscopic dilation and endoluminal cryotherapy.